شبهات جولدرزيهر حول القراءات القرآنية في كتاب " مذاهب التفسير الإسلامي" - وان حسن بن وان أحمد (al-Jami'ah al-Islamiyah al-'Alamiyah bi-Maliziya, 2005)
This study examines Goldziher's skepticism on al-Qira’at al-Qur’aniyyah (multiple reading of the Qur’an) in his book entitled "Madhahib al-Tafsir al-Islami" (Islamic exegesis sects). It analyzes Goldziher's assertions related to the divergence in the reading of the Qur’an and his style in presenting those assertions. This study aims to refute Goldziher’s skepticism that has influenced in his study of al-Qira’at. This study relies upon deductive and analytic methodologies by analyzing all relevant data. This study employs comparative methodology when comparing the approach used by Goldziher and the Qurra’ in approving the authenticity of Qira’at. The findings of this study show that Goldziher did not rely upon the scientific evidence for his assertions on the divergence of al-Qira’at, rather he relied on his personal precepts, sentiments and emotions in its stead, which is totally invalid in the study of the Qira’at. In addition, he also did not use the scientific methodology, which had been applied by the Qurra’ in approving the Qira’at.